Eine empirische Untersuchung von Business-to-Business Online Bewertungen - Müller, Tobias Sören

Greta’s Gonna Wake Them Up? – An Empirical Analysis of the Im-pact of Greta Thunberg’s Global Climate Strike on Donations for Environmental Charitable Crowdfunding Campaings - Okumus, Hasan

Deutsch für den Beruf [Sammelrezension] Sander, Isa-Lou; Efing, Christian (Hrsg.): Der Betrieb als Sprachlernort. Tübingen: Narr Francke Attempto, 2021 (Kommunizieren im Beruf, 4). -- ISBN 978-3-8233-8442-7. 264 Seiten, € 68,00. Tichy, Ellen; Tesch, Felicitas (Hrsg.): Deutsch in Fach und Beruf. Aktuelle Fragen und neue Ansätze der Fremdsprachenvermittlung. Berlin: Peter Lang, 2021 (Berufssprache Deutsch in Theorie und Praxis, 2). -- ISBN 978-3-631-79553-8. 194 Seiten, € 49,95. Niederhaus, Constanze: Deutsch für den Beruf. Eine Einführung. Berlin: Erich Schmidt, 2022 (Grundlagen Deutsch als Fremd- und Zweitsprache, 4). -- ISBN 978-3-503-20545-5. 265 Seiten, € 22,00. - Prikoszovits, Matthias (Informationen Deutsch als Fremdsprache)
Keywords: General Medicine

Infrastrukturen der Anerkennung. Eine Theorie sozialer Medienplattformen - Schulz, Christian

SNAPE: A Sequential Non-Stationary Decision Process Model for Adaptive Explanation Generation - Robrecht, Amelie; Kopp, Stefan (Proceedings of the 15th International Conference on Agents and Artificial Intelligence)

“Sorry, Too Much Information”. Designing Online Review Systems that Support Information Search and Processing - Seutter, Janina; Kutzner, K.; Stadtländer, M.; Kundisch, Dennis; Knackstedt, R. (Electronic Markets)

Untersuchung des Reibungs- und Deformationsverhaltens von schnelllaufenden Bremsen - Rauhaus, Johann; Schadomsky, Magnus; Magyar, Balázs; Zimmer, Detmar (Tagungsband der 64. Tribologie-Fachtagung)

Evidenzbasierte Hochschuldidaktik - Scharlau, Ingrid; Jenert, Tobias (Hochschuldidaktik als Wissenschaft: Disziplinäre, interdisziplinäre und transdisziplinäre Perspektiven)

Interdependency study of design guidelines - Hesse, Philipp; Gräßler, Iris (Climate Protection, Resource Efficiency, and Sustainable Engineering: Transdisciplinary Approaches to Design and Manufacturing technology.)

Sustainable product life cycle - Hesse, Philipp; Gräßler, Iris (Climate Protection, Resource Efficiency, and Sustainable Engineering: Transdisciplinary Approaches to Design and Manufacturing technology.)

Polymeric Networks Containing Amine Derivatives as Organocatalysts for Knoevenagel Reaction within Continuously Driven Microfluidic Reactors - Killi, Naresh; Bartenbach, Julian; Kuckling, Dirk (Gels)
The Knoevenagel reaction is a classic reaction in organic chemistry for the formation of C-C bonds. In this study, various catalytic monomers for Knoevenagel reactions were synthesized and polymerized via photolithography to form polymeric gel dots with a composition of 90% catalyst, 9% gelling agent and 1% crosslinker. Furthermore, these gel dots were inserted into a microfluidic reactor (MFR) and the conversion of the reaction using gel dots as catalysts in the MFR for 8 h at room temperature was studied. The gel dots containing primary amines showed a better conversion of about 83–90% with aliphatic aldehyde and 86–100% with aromatic aldehyde, compared to the tertiary amines (52–59% with aliphatic aldehyde and 77–93% with aromatic aldehydes) which resembles the reactivity of the amines. Moreover, the addition of polar solvent (water) in the reaction mixture and the swelling properties of the gel dots by altering the polymer backbone showed a significant enhancement in the conversion of the reaction, due to the increased accessibility of the catalytic sites in the polymeric network. These results suggested the primary-amine-based catalysts facilitate better conversion compared to tertiary amines and the reaction solvent had a significant influence on organocatalysis to improve the efficiency of MFR.
Keywords: Knoevenagel reaction; organocatalysis; polymeric gel dots; microfluidic reactions; polymeric networks

Asymptotics for the infinite Brownian loop on noncompact symmetric spaces - Papageorgiou, Efthymia (Journal of Elliptic and Parabolic Equations)
Abstract The infinite Brownian loop on a Riemannian manifold is the limit in distribution of the Brownian bridge of length T around a fixed origin when $$T → +∞ $$ T → + ∞ . The aim of this note is to study its long-time asymptotics on Riemannian symmetric spaces G / K of noncompact type and of general rank. This amounts to the behavior of solutions to the heat equation subject to the Doob transform induced by the ground spherical function. Unlike the standard Brownian motion, we observe in this case phenomena which are similar to the Euclidean setting, namely $$L^1$$ L 1 asymptotic convergence without requiring bi- K -invariance for initial data, and strong $$L^{∞ }$$ L ∞ convergence.
Keywords: Applied Mathematics; Numerical Analysis; Analysis

A 28-Gb/s 27.2mW NRZ Full-Rate Bang-Bang Clock and Data Recovery in 22 nm FD-SOI CMOS Technology - Iftekhar, Mohammed; Gowda, Harshan; Kneuper, Pascal; Sadiye, Babak; Müller, Wolfgang; Scheytt, Christoph (2023 IEEE BiCMOS and Compound Semiconductor Integrated Circuits and Technology Symposium (BCICTS))

On-The-Fly Computing -- Individualized IT-services in dynamic markets - Haake, Claus-Jochen; Meyer auf der Heide, Friedhelm; Platzner, Marco; Wachsmuth, Henning; Wehrheim, Heike
In the proposal for our CRC in 2011, we formulated a vision of markets for IT services that describes an approach to the provision of such services that was novel at that time and, to a large extent, remains so today: „Our vision of on-the-fly computing is that of IT services individually and automatically configured and brought to execution from flexibly combinable services traded on markets. At the same time, we aim at organizing markets whose participants maintain a lively market of services through appropriate entrepreneurial actions.“ Over the last 12 years, we have developed methods and techniques to address problems critical to the convenient, efficient, and secure use of on-the-fly computing. Among other things, we have made the description of services more convenient by allowing natural language input, increased the quality of configured services through (natural language) interaction and more efficient configuration processes and analysis procedures, made the quality of (the products of) providers in the marketplace transparent through reputation systems, and increased the resource efficiency of execution through reconfigurable heterogeneous computing nodes and an integrated treatment of service description and configuration. We have also developed network infrastructures that have a high degree of adaptivity, scalability, efficiency, and reliability, and provide cryptographic guarantees of anonymity and security for market participants and their products and services. To demonstrate the pervasiveness of the OTF computing approach, we have implemented a proof-of-concept for OTF computing that can run typical scenarios of an OTF market. We illustrated the approach using a cutting-edge application scenario – automated machine learning (AutoML). Finally, we have been pushing our work for the perpetuation of On-The-Fly Computing beyond the SFB and sharing the expertise gained in the SFB in events with industry partners as well as transfer projects. This work required a broad spectrum of expertise. Computer scientists and economists with research interests such as computer networks and distributed algorithms, security and cryptography, software engineering and verification, configuration and machine learning, computer engineering and HPC, microeconomics and game theory, business informatics and management have successfully collaborated here.

Gegen das Verstummen. Texthermeneutische Reflexionen zu Ironie in der Textsortenwelt des Gettos Litzmannstadt - Markewitz, Friedrich
Unmittelbar nach der nationalsozialistischen Machtergreifung setzte eine umfassende gesellschaftliche, juristische und existentielle Ausgrenzung jüdischer Akteure ein. Dem Zerbrechen bisheriger Welt- und Normverständnisse zu begegnen wurde zu einer existentiellen Herausforderung sowie zu einem notwendigen Bedürfnis. Eine wichtige Strategie war der Einsatz von Humor und Ironie; auch für die Menschen des Gettos Litzmannstadt. Aus texthermeneutischer, kulturlinguistischer und sprachphilosophischer Perspektive erfasst Friedrich Markewitz – unter Berücksichtigung des Gettos als Diskursraum und dessen Textsortenwelt – Verwendungsweisen und -funktionen von Ironie und perspektiviert sie, um so einen Beitrag zur linguistischen Aufarbeitung der Kommunikation jüdischer Akteure während der Shoa zu leisten.

Kommunikative Praktiken im Nationalsozialismus
Die nationalsozialistische Gesellschaft war geprägt von vielgestaltigen kommunikativen Praktiken des sozialen und auch gewaltvollen Ein- und Ausschlusses. Gleichzeitig bildeten sich durch Widerstandshandlungen vielfältige Gegendiskurse heraus. Der Sammelband nimmt konkrete Beispiele kommunikativer Praktiken während des Nationalsozialismus in den Blick und fragt speziell danach, inwiefern diese themen-, textsorten- und akteursspezifisch gebunden waren

A hesitant fuzzy group decision-making framework with data credibility and strategic evaluations - Tavana, Madjid; Keikha, Abazar; Santos-Arteaga, Francisco J. (Soft Computing)

Dear Guests, please pay for my license – Analyzing the heterogenous cost-pass-through of commercial and non-commercial rental suppliers in response to regulatory policies - Müller, Michelle; Neumann, Jürgen; Kundisch, Dennis (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Moment or Movement – An Empirical Analysis of the Heterogeneous Impact of Media Attention on Charitable Crowdfunding Campaigns - Seutter, Janina; Müller, Michelle; Müller, Stefanie Jutta Marianne; Kundisch, Dennis (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Governance and Reputation in the Market for Experience Goods - Fanasch, Patrizia